Schimmelpenning-Feuerstein-Mims syndrome: a systematic review of clinical cases to identify genotype-phenotype associations - Zelenova, Ekaterina; Belysheva, Tatiana; Sharapova, Elena; Semenova, Vera; Valiev, Timur; Nasedkina, Tatiana (Frontiers in Medicine, 2025)
Background/objectivesSchimmelpenning-Feuerstein-Mims syndrome (SFMS) is a rare genodermatosis from the group of epidermal nevus syndromes with a wide range of clinical manifestations, including linear nevus sebaceous, ophthalmological disorders, cardiovascular abnormalities, nervous system and musculoskeletal system lesions. Benign and malignant neoplasms, precocious puberty, lymphedema and malformations of the lymphatic system may also be present. The main cause of the syndrome are postzygotic mutations in the RAS pathway, namely in the HRAS, KRAS, and NRAS genes. The aim of our work was to analyze previously described and genetically confirmed clinical cases of SFMS in order to reveal genotype-phenotype correlations.MethodsA systematic literature review (SLR) was conducted in several databases, including PubMed and ResearchGate to search for clinical cases of SFMS with genetic testing data from 1946 to 2025. The criterion for inclusion was considered to be the reference to SFMS or its synonyms in article titles with no limitations on language or date of publication. Also, no restrictions on patient age, ethnicity, presence/absence of photo-materials were applied. Only original articles reporting clinical case or case series with detection of postzygotic mutations in the HRAS, KRAS or NRAS genes were included.ResultsCurrently, 50 patients with SFMS and identified pathogenic variants in the HRAS (n = 17), KRAS (n = 30), or NRAS (n = 3) genes have been described in the literature. Analyzing presented phenotypic features of genetically confirmed cases of SFMS depending on the affected gene, we found that ophthalmological and central nervous system anomalities were more common for the KRAS-mut patients (p < 0.05). In contrast, patients with HRAS mutations were more likely to have skeletal abnormalities (p < 0.05). Benign and malignant tumors were diagnosed with equal frequency in both genetic groups, but renal tumors were strongly associated with KRAS mutations.ConclusionThe data obtained indicates the necessity of genetic testing for all patients suspected of SFMS to determine the individual risk of comorbidities and to form a personalized plan for dynamic follow-up.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD420251085872, identifier CRD420251085872.